Synthesis and biological evaluation of phenanthrenes as cytotoxic agents with pharmacophore modeling and ChemGPS-NP prediction as topo II inhibitors. - Chia-Lin Lee (Public Library of Science (PLoS), 2012)
In a structure-activity relationship (SAR) study, 3-methoxy-1,4-phenanthrenequinones, calanquinone A (6a), denbinobin (6b), 5-OAc-calanquinone A (7a) and 5-OAc-denbinobin (7b), have significantly promising cytotoxicity against various human cancer cell lines (IC(50) 0.08-1.66 µg/mL). Moreover, we also established a superior pharmacophore model for cytotoxicity (r = 0.931) containing three hydrogen bond acceptors (HBA1, HBA2 and HBA3) and one hydrophobic feature (HYD) against MCF-7 breast cancer cell line. The pharmacophore model indicates that HBA3 is an essential feature for the oxygen atom of 5-OH in 6a-b and for the carbonyl group of 5-OCOCH(3) in 7a-b, important for their cytotoxic properties. The SAR for moderately active 5a-b (5-OCH(3)), and highly active 6a-b and 7a-b, are also elaborated in a spatial aspect model. Further rational design and synthesis of new cytotoxic phenanthrene analogs can be implemented via this model. Additionally, employing a ChemGPS-NP based model for cytotoxicity mode of action (MOA) provides support for a preliminary classification of compounds 6a-b as topoisomerase II inhibitors.